Effect of glaze and chlorhexidine on physical and mechanical properties of bis-acryl resin: An in situ study - Commar, Betina Chairelo [UNESP]; Danelon, Marcelle [UNESP]; Panitente, Paulo Augusto [UNESP]; Silva, Emily Vivianne Freitas Da [UNESP]; Bitencourt, Sandro Basso [UNESP]; Barão, Valentim Adelino Ricrdo; Neto, Clóvis Lamartine De Moraes Melo [UNESP]; Goiato, Marcelo Coelho [UNESP]; Santos, Daniela Micheline dos [UNESP] (Wroclaw Medical University, 2022)
BACKGROUND: Temporary prosthesis protects the oral tissues, in addition to providing aesthetic look and masticatory function until a definitive prosthesis is manufactured. OBJECTIVES: To evaluate the effect of glaze and 0.12% chlorhexidine (CHX) on the physical and mechanical properties of bis-acryl, and to evaluate the antimicrobial efficacy of CHX. MATERIAL AND METHODS: Eighty specimens of bis-acryl resin were made. Over 40 of them the glaze was applied. One specimen with and 1 specimen without glaze were placed in niches of an appliance manufactured for each patient. Each of the 20 volunteers received 2 devices. Initially, the volunteers used one device and treated it with sucrose for 7 days (control), and later they used the other device and treated it with sucrose and CHX for 7 days (test). Color, microhardness, roughness, surface energy, and insoluble extracellular polysaccharides (EPS) tests were performed. All results were submitted to the Tukey's test, with the exception of the EPS results, which were submitted to the Student's t test. RESULTS: The ΔE00 of the unglazed control group was significantly higher than that of the unglazed test group. In all groups, a significant decrease in microhardness occurred over time. At both times, the glaze significantly increased the microhardness of the specimens (in all the glazed groups). At the final time, the test glaze group showed significantly higher microhardness compared with the control glaze group. Roughness in the groups without glaze increased significantly with CHX treatment over time. At both times, the glaze generated a significant reduction in roughness in the control and test groups. There was a significant reduction in surface energy over time in all groups. In most comparisons, the glazed groups showed significantly higher surface energy values compared with the unglazed control group. At the final time point, the unglazed test group showed a significantly higher surface energy value than the unglazed control group; and the glazed test group showed a significantly higher surface energy value compared with the glazed control group. The resins that received CHX had a significantly lower amount of biofilm. CONCLUSIONS: Color values were clinically acceptable in all tested groups. At both time points, the roughness values were clinically acceptable only in the glazed groups. Glaze increased the microhardness of the specimens. Microhardness and surface energy were reduced over time in all groups. Chlorhexidine can help prevent microhardness degradation. Glaze and CHX can increase surface energy. Chlorhexidine reduced the amount of bacterial biofilm.
Keywords: bacterial adhesion; dental biofilm; surface property; temporary dental restorations